MY LIFE WITH THE WALTER BOYS - Novak, Ali, 1991- (Naperville, Illinois, Sourcebooks Fire, Naperville, Illinois, 2024)
"Jackie's goal is perfection--perfect grades, the perfect look, getting into the perfect school. If she can achieve that, then maybe her too-busy mom and dad will take notice. But when her parents die in a tragic accident, Jackie is shipped off across the country to live with the Walters, her new guardians...who just happen to have eleven sons (plus a daughter who is basically one of the boys)."-- Provided by publisher
"A Netflix series"--Cover
Keywords: Parents -- Death -- Fiction; Home -- Fiction; Grief -- Fiction; Brothers -- Fiction; Dating -- Fiction; Romance fiction; Young adult fiction